PRE-SOWING TREATMENT OF SUNFLOWER, SOYBEAN AND MAIZE SEEDS WITH LOW-FREQUENCY ELECTROMAGNETIC RADIATION - N. S. Levina; Yu. V. Tertyshnaya; I. A. Bidey; O. V. Elizarova (Сельскохозяйственные машины и технологии, 2018)
Pre-sowing  seed treatment by various energy methods is used as an effective way of stimulating the seed material. (Research purpose) The authors have studied the effect of a low-frequency electromagnetic field on the seed properties of sunflower (Helianthus), soybean (Glycine max) and maize (Zea mays L.) seeds. (Materials and methods) Parameters of the electromagnetic field: induction of 16 mT, pulse repetition rate of 16 Hertz I; exposure time of 15 and 20 minutes. The experiment has been conducted in two stages. The first stage is the determination of the germination and germination energy of irradiated and non-irradiated seeds, as well as the biometric characteristics of seedlings: the mass of stems and leaves, the length and mass of the root system. The second stage is the phenological observations of the growth and development of plants according to the phases of their development in the VIM climatic chamber. (Results and discussion) It has been shown that the sowing qualities of maize seeds after 15 min of irradiation are higher than the control ones. It has been determined that germination energy has increased by 10 percent as compared to the control sample, germination by 8 percent, seedling weight by 6.4 percent, weight of stems and leaves by 16, root system by 3.4 and stem height by 30 percent. It has been found that there is no influence of low-frequency electromagnetic radiation on the germination of soybeans both in the laboratory and in the climate chamber. It has been found that at the end of the growing season, the mass of plants irradiated for 20 minutes has turned out to be greater than the control values by 20%, the root mass by 25%, and the root length by 16%. The authors have determined that the treatment of sunflower seeds (Helianthus) with a low-frequency electromagnetic field has no stimulating effect on germination energy and germination capacity, but contributes to an increase in the mass of plants when they are grown in a phytotron. It has been calculated that a 15-minute irradiation of sunflower seeds before sowing resulted in an increase in the mass of plants by 34.9%; the mass of the root system – by 22%; length of roots – by 3.65%; the head (anthodium)  diameter – by 5.3% and their weights – by 25.3 %. (Conclusions) The response of plants to the energy impact depends on the type of crop. It has been determined that low-frequency magnetic radiation without changing the sowing properties of seeds can positively influence the growth and development of plants.